Analysis of Employee Procurement Process: Case Study at CIMB Niaga Bank of Banjarmasin - Shifa Fauzia; Meldasari Said (CV. Media Digital Publikasi Indonesia, 2023)
This study aims to analyze the employee recruitment and selection process at CIMB Niaga Bank of Banjarmasin and the effect to the employee performance. The research used a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results showed that CIMB Niaga Banjarmasin uses an open and closed recruitment process through internal and external sources, and uses both scientific and non-scientific methods in selecting employees. Job announcements have taken advantage of technology and social media. However, the selection method used is still conservative. It was found that recruitment and selection have an impact on the performance of employees at CIMB Niaga Bank Banjarmasin.. This proves that scientific recruitment methods such as psychological tests can predict the performance of prospective employees in the future